Beiträge zur Insekten-Fauna der DDR: Lepidoptera - Argyresthiidae. - Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1969)
On the basis of arevision of all available collections, the author’s collection and a critical evaluation of the relevant publications, a faunistic survey of the Argyresthiidae on the territory of the GDR is given, subdivided for the districts. A total of 25 species are listed from 1748 founds. 1896 pattern were studied altogether. A key is supplied which together with the illustrations will facilitate the determination of the discussed species.